THE HUMAN HAIR FOLLICLE AS SENTINEL FOR DRUGS EVALUATION: DEMONSTRATION OF TETRACYCLINE ADHESION TO HAIR FOLLICLE AS PROPOSED MECHANISM IN DYSFUNCTIONAL HAIR LOSS - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2020)
One mechanism of action of antibiotics such as tetracyclines involves the disruption of pathogens cell membranes. This author had previously demonstrated in vitro and in vivo the utility of a human miniorgan, a.k.a. hair follicle as sentinel in demonstrating the deleterious effect of alcohol by showing a disruption in metabolism. In this manuscript, the hair follicle was again used in vitro as sentinel in direct contact with another exogenous substance in two forms, namely liquid and powder tetracycline. The results demonstrate the adhesion property of tetracycline as a mechanism causing deleterious effect on the biological active cells of the follicle’s dermal papilla, and the consequent disruption in metabolism. Notably, it was documented a strong affinity of the antibiotic to the keratin skeleton of the hair follicle. In a recent published report, the adverse effect of tetracycline induction on experimentally deficient mitochondrial DNA (mtDNA) mouse was reversed and documented 30 days after discontinuation of the tetracycline diet. The experiments herein presented correlate and confirm previous findings of long term exposure to tetracycline causing not only damage the pathogen; but also healthy human cells. Since mtDNA may play a role in aging and age-associated diseases: Beware of tetracycline therapy on the elderly.